Bilateral Elastofibrolipoma: Distinguishing from Elastofibroma with Adipose Tissue Migration - Betül Ünal; Ali Uzar; Murat Şedele; Bekir Erol (Hindawi Limited, 2015)
We present a case of a 54-year-old female patient. MRI examination showed a mass adjacent to the left scapula and a localized heterogeneous mass in the right subscapular area. Microscopic examination revealed abnormal elastic fibers and globules and mature adipose tissue mixed with collagen bands in all areas of the lesion. Genetic analysis was done and there were no changes in DNA copy number. The lesion was diagnosed as elastofibrolipoma which is a rare tumor. No bilateral elastofibrolipoma has been previously described.